The terms of address as speech stereotypes in Korean. (Journal of Oriental Studies, 2016)
This article describes the terms of address as speech stereotypes in the Korean. The speech stereotypes are used in the finished form and bear the additional connotation. There is specific cultural background behind the national stereotypes: not reported literal meaning of a lexical unit, but understandable for participants of communication. For example, the use of the name in Korean language has familiarity connotation in connection with which reference by name is considerable limited. Instead of address by name stereotyped in Russian, in Korean a variety of social, family and other forms of address are used.
Keywords: korean language; national stereotypes; use of the mane in korean language; addresses